Decomposition of exponential sums based on subspace and its application in channel estimation - Zhiwei WU; Haiquan WANG; Meihui LI; Xinyu ZHANG; Taoxin QIAN (Dianxin kexue)
The problem of the decomposition of an exponential sum sequence is a classical mathematical problem.Prony method and Prony-Kung method are the classical methods to solve this problem.The Prony-Kung method was analyzed in detail from the point of view of support subspace.On this basis, it was proved theoretically that the problem of the decomposition of an exponential sum sequence could be reduced to the determination of the support subspace, and a Lloyd-like algorithm with low-complexity for searching the support subspace for contaminated exponential sum sequence by noised was proposed.Finally, the above algorithm was applied to estimate millimeter wave channel, and the simulation results show the effectiveness of this application.